Propuesta de un modelo de gestión por competencias en la selección del talento humano en el GAD del cantón Pedernales - Hidrovo Zambrano, Jean Pierre (2025)
The main objective of this research was to analyze and promote the implementation of a competency-based management model to optimize the human talent selection process at the Decentralized Autonomous Government (GAD) of the Pedernales canton. A qualitative methodology with a descriptive approach was applied, supported by inductive, deductive, analytical, and synthetic methods. The main techniques used were an interview with the Human Talent Director and surveys administered to department heads and GAD officials. Among the most relevant results, it was identified that the GAD lacks standardized selection processes aligned with competency profiles, which limits objectivity, efficiency, and transparency in personnel recruitment. Furthermore, it was found that the current internal regulations are insufficient and do not align with national technical guidelines. Based on this diagnosis, a competency-based management model was proposed, including technical, behavioral, leadership, and adaptability dimensions suited to the institutional context. It is concluded that the implementation of this model would significantly strengthen the human talent selection process, aligning job profiles with institutional objectives and improving organizational performance. Likewise, it is recommended to update internal regulations and train the responsible personnel in the competency-based approach to ensure the sustainability of the model.